Key Drivers of State Preemption of Food, Nutrition, and Agriculture Policy: A Thematic Content Analysis of Public Testimony. Issue 6 (July 2019) - Pomeranz, Jennifer L.; Pertschuk, Mark
Purpose: Local communities are often active public health policy makers, so state preemption—when the state withdraws authority from local governments—can hinder public health progress. Kansas enacted the most sweeping law in the nation preempting food, nutrition, and agricultural policy. Design: Qualitative thematic content analysis was used on public comments to identify and evaluate common and key arguments. A codebook was developed using an iterative process. Open coding was applied to all comments. Setting: All testimony and comments submitted by individuals and organizations to the Kansas State Legislature on the preemptive bill. Participants: Eight types of commentators submitted 34 written and 12 oral comments. Measures: The data were evaluated on a latent level to examine underlying drivers of preemption. Results: Comments addressed 18 themes, referenced 366 times; 68% in opposition. Common themes included local control, food labeling, public health, need for statewide standards, and debate over food regulation. Key themes included the need for state and federal uniformity to support businesses and consumers, debate over topics not in the bill, the value of local control, confusion over bill coverage, and outside influences. Conclusion: Confusion about bill language and coverage, the combination of food and agricultural issues, and backing by multinational corporations helped propel preemption forward in Kansas. Food policy stakeholders nationally can anticipate similar arguments and strategies in their state.